A COGNITIVE-LINGUISTIC ANALYSIS OF WISH AND DESIRE CONCEPTS IN ENGLISH AND UZBEK LEXICAL SYSTEMS - Zarnigor Nasriddinovna, Sirojova (Advances in Science and Humanities, 2026)
The present study examines how the concepts of wish and desire are structured, categorized, and lexically expressed in English and Uzbek from a cognitive-linguistic perspective. We argue that the conceptualization of these volitional states is not universal but is shaped by the cultural and cognitive models embedded in each language. Drawing on prototype theory, conceptual metaphor theory, and the notion of radial categories, we analyze a set of lexical units — including wish, desire, hope, want, orzu, istak, umid, and armon — and trace the cognitive paths through which speakers of each language construct and communicate inner volitional experience. Our findings reveal that English organizes wish and desire around a relatively individualistic, achievement-oriented cognitive model. In contrast, Uzbek encodes these concepts through frameworks rooted in communal values, patience, and spiritual aspiration. These cross-linguistic differences carry meaningful implications for contrastive linguistics, cultural semantics, and the broader study of language and thought.